Real-life study to assess effectiveness and safety of eculizumab in patients with neuromyelitis optica spectrum disorders in France: protocol for ECUP4, an observational study - Marignier, Romain; Laplaud, David; Zéphir, Hélène; Papeix, Caroline; Leray, Emmanuelle; Amri, Ekbel; Piotaix, Mickaël; de Sèze, Jérôme (Frontiers in Neurology, 2024)
Background Eculizumab, a humanized monoclonal antibody targeting the C5 complement protein, has been approved for the treatment of neuromyelitis optica spectrum disorders (NMOSD) in adult patients who are anti-aquaporin-4 (AQP4) antibody positive (Ab+). The aim of this study is to evaluate the long-term effectiveness and safety of eculizumab in French adults with NMOSD and to describe patients' characteristics, disability, and quality of life using data collected in a real-world setting. Methods This is the protocol for ECUP4, an ongoing prospective, observational, non-comparative, multicenter study conducted in 32 reference centers in France. Eligible patients must also be enrolled in NOMADMUS, a nested cohort of the French national multiple sclerosis registry (OFSEP). The primary endpoint is the annualized relapse rate. Secondary endpoints include the long-term safety of eculizumab, as well as patients' characteristics, treatment outcomes, disability, pain, visual acuity, and quality of life. Visits and treatments follow routine clinical practice. The case report forms (CRF) comprise data recorded in the context of the NOMADMUS cohort, collected during routine visits. The inclusion period is planned for 3 years, with no limitation on the number of patients enrolled. The maximum follow-up duration will be 5.5 years. Conclusion The efficacy and safety of eculizumab in patients with AQP4+ NMOSD have been demonstrated in randomized clinical trials that showed a significant reduction in the risk of relapse, with a safety profile consistent with other indications. This study will provide clinical and patient-reported evidence of the benefits of eculizumab, using data from a real-world setting in France. Trial registration number This study is registered at the French public repertory Health data Hub, N° F20211228123801. All information can be accessed at: https://www.health-data-hub.fr/.